J01 EHDN standards of care occupational therapy guidelines. (16th November 2010) - Cook, C; Page, K; Wagstaff, A; Rae, D; Simpson, S A
Abstract : Background: Occupational Therapy is an essential component of the management of patients with Huntington's disease throughout the progression of the disease. Occupational therapists aim to enable individuals to maximise function in everyday activities and to maintain independence. Aims: The European Huntington's Disease Network's (EHDN) Occupational Therapist group has brought together a group of international OT's to provide guidelines to encourage thorough assessment and management of individuals throughout the course of their disease. The guidelines were developed to promote independence for individuals with HD as well as their carers and family and to maximise quality of life. Method: A systematic literature search was performed electronically. Due to the limited scope of the literature found, observational studies and qualitative studies were included in the review process. Recommendations were formulated based upon clinical experience and expert consensus from within the EHDN Standards of Care Occupational Therapist group. Results: The first edition of the guideline has been produced and is awaiting publication. The main guideline incorporates the areas of self care, work and leisure. It details possible difficulties, specific interventions and rationale in those areas. Furthermore, the guideline also advises on occupational therapy assessment tools and points to consider when using specific types of equipment. Conclusion: This document was produced within a short time line and will be refined further and updated as necessary. It is currently being prepared for verification by the College of Occupational Therapists in the UK and will also be implemented across Europe.